OVERWEIGHT AND OBESITY CHILDREN IN PRIVATE ELEMENTARY SCHOOL OF SOUTH JAKARTA - Fitri Annisa; Eni Sumartini (JURNAL KEPERAWATAN CIKINI, 2021)
Strategies for overweight and obesity in school-age children need more attention from the government. We need basic data to determine the right strategy in dealing with overweight and obesity in school-age children. The purpose of this study was to know the proportion of overweight and obesity in private elementary students in South Jakarta. This study used a cross-sectional design, with a total of 400 samples. Samples were taken by multistage sampling with several steps grouping. The results showed that in private elementary schools, the rates of overweight (17.0%) and obesity (30.75%). Based on the results of this study, the government needs different strategies in overcoming overweight and obesity in private elementary schools. Further research is needed related to things that influence the occurrence of obesity in private school students.